2020
DOI: 10.3390/nano10112238
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Sheets as Inhibitors of the Photochemical Reactions of α-Lipoic Acid in the Presence of Ag and Au Nanoparticles

Abstract: The influence of Ag and Au nanoparticles and reduced graphene oxide (RGO) sheets on the photodegradation of α-lipoic acid (ALA) was determined by UV-VIS spectroscopy. The ALA photodegradation was explained by considering the affinity of thiol groups for the metallic nanoparticles synthesized in the presence of trisodium citrate. The presence of excipients did not induce further changes when ALA interacts with Ag and Au nanoparticles with sizes of 5 and 10 nm by exposure to UV light. Compared to the Raman spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…ALA that has interacted with Au with sizes of 5 and 10 nm, the UV-VIS spectra were characterized by absorption bands with a maximum at 322 nm and 542 nm. In the case of ALA that has interacted with Au nanoparticles with a size of 10 nm, these bands were situated at 320 nm and 530 nm in the case of ALA that has interacted with Au nanoparticles with a size of 5 nm [ 26 ]. Toulbe et al suggested the higher affinity of thiol groups of ALA for silver (Ag) nanoparticles compared with that for Au nanoparticles [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALA that has interacted with Au with sizes of 5 and 10 nm, the UV-VIS spectra were characterized by absorption bands with a maximum at 322 nm and 542 nm. In the case of ALA that has interacted with Au nanoparticles with a size of 10 nm, these bands were situated at 320 nm and 530 nm in the case of ALA that has interacted with Au nanoparticles with a size of 5 nm [ 26 ]. Toulbe et al suggested the higher affinity of thiol groups of ALA for silver (Ag) nanoparticles compared with that for Au nanoparticles [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ALA that has interacted with Au nanoparticles with a size of 10 nm, these bands were situated at 320 nm and 530 nm in the case of ALA that has interacted with Au nanoparticles with a size of 5 nm [ 26 ]. Toulbe et al suggested the higher affinity of thiol groups of ALA for silver (Ag) nanoparticles compared with that for Au nanoparticles [ 26 ]. The formation of the thiolate-gold clusters is explained by several models reported by Walter et al [ 27 ] who considered the magic numbers of free valence electrons and Cheng et al [ 28 ] who considered the super-atom network and the super-valence bond mode preferential chemical adsorption of ALA onto metallic nanoparticles, as reported in the case of other thiols [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a promising 16-fold increase in capacitance as compared to the preceding GO nanofibers. Another entry on reduced GO has been reported by Toulbe et al [7], who have found that this nanomaterial is capable of inhibiting the photodegradation of α-lipoic acid (an antioxidant) in the presence of Au and Ag nanoparticles, with important implications in pharmaceutical compounds. As a complementary insight into both of the aforementioned studies, Tene and co-workers present an elegant study on how the drying conditions of GO critically affect its structure and nature of defects [8].…”
mentioning
confidence: 88%